Consequences of childhood reading difficulties and behaviour problems for educational achievement and employment in early adulthood. (7th March 2017) - Smart, Diana; Youssef, George J.; Sanson, Ann; Prior, Margot; Toumbourou, John W.; Olsson, Craig A.
Abstract : Background: Reading difficulties (RDs) and behaviour problems (BPs) are two common childhood problems that have a high degree of stability and often negatively affect well‐being in both the short and longer terms. Aims: The study aimed to shed light on the unique and joint consequences of these two childhood problems for educational and occupational outcomes in early adulthood. Sample: Data were drawn from a life‐course longitudinal study of psychosocial development, the Australian Temperament Project. Methods: Parent and teacher reports and a standard reading test were used to define four groups of children at 7–8 years: RDs only; BPs only; both problems; and neither problem. These groups were followed forward to ascertain educational attainment and employment status at 19–20 and 23–24 years. Results: Each childhood problem was a unique risk for poorer educational and occupational outcomes, with co‐occurring problems significantly increasing the risk of poorer educational outcomes. Further analyses revealed that the effects of childhood BPs on occupational status were mediated by secondary school non‐completion, but childhood RDs were not. Conclusions: The findings point to the importance of screening and early intervention to prevent or minimize the development of these two childhood problems, as well as continuing to support vulnerable children to increase their likelihood of secondary school completion.